Assessing Service Quality of Inpatient Community Health Center and Its Impact on Patient Satisfaction: A SERVQUAL and Zone of Tolerance Approach - Kuncoro, Shienny; Fristiohady, Adryan; Wahyuni, Wahyuni; Ruslin, Ruslin; Amran, Mulyaty (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Community Health Center Poasia, as a public service, aims to provide quality health services. The existence of complaints from patients related to the services received can have an impact on patient visits, which in 2023 decreased by around 21%. One of the causes of decreased patient visits is that patients are not satisfied with the services at the Poasia Health Center. The quality of health services can be measured using the Servqual and ZoT methods. The Servqual method measures the GAP value between the performance value and the expected value, followed by ZoT to see whether the tolerance limit range of patient dissatisfaction is still acceptable. Respondents will be interviewed using a questionnaire. The results of this study showed that the GAP value in the responsiveness dimension is still negative (-0.04), indicating that some patients are dissatisfied with the services received. The GAP value for the other four dimensions is positive, indicating that patients are satisfied with the services received at the health center. The ZoT value in the tolerance limit range is -0.01-2.24. The negative ZoT value indicates that some patients are dissatisfied, and the positive ZoT value of the patient is still within the tolerance limit for receiving minimum service. This study concludes that quality health services will provide satisfaction to patients.